ANALISIS DAYA SAING USAHATANI KELAPA SAWIT RAKYAT DI KECAMATAN PELEPAT KABUPATEN BUNGO - Adhe Poetera Damanik, Sopiyan; Murdy, Saad; Saputra, Ardhiyan (Jurnal Ilmiah Sosio-Ekonomika Bisnis, 2019)
This research is intended to analyze (1) competitiveness (competitive advantage and comparative advantage), (2) the impact of government policies on output and input, and (3) competitiveness sensitivity in smallholder palm oil farming in District of Pelepat, Bungo Regency. The analytical methods used in this research were Net Present Value and Policy Analysis Matrix. The research was held on February 21st 2016 until March 30th 2016. The results showed that: (1) Smallholder palm oil farming in District of Pelepat, Bungo Regency had competitive advantage with the value of PP > 0 and PCR = 0.19, also had comparative advantage with the value of SP > 0 and DRCR = 0.13; (2) Government policies were unprotective and disincentive to output because the value of NPCO is 0.67, government policies on tradable input were protective because the value of NPCI is 0.71, and government policies were overall disincentive to palm oil commodity because the value of PC = 0.61, EPC = 0.66, and SRP -0.31; and (3) Smallholder palm oil farming still had competitiveness if the price of output fell down by 50 percent because the value of PCR = 0.43 and DRCR = 0.29, if the price of input risen up by 6.38 percent because the value of PCR = 0.21 and DRCR = 0.14, and even if both simulations were happened at the same time, because the value of PCR = 0.46 and DRCR = 0.30